Malmbanan Diaries - Andersson, Sarah; Butler, Andrew; Calderon, Camilo; Cerwén, Gunnar; Dabaieh, Marwa; Deak, Johanna; Hellström Reimer, Maria; Johansson, Anders; Johansson, Rolf; Larsson, Anders; Lieberg, Mats; Lindholm, Gunilla; et al. (Swedish University of Agricultural Sciences, 2010)
This booklet is a report for a case study visit during four day field trip, a group of nine PhD students and their supervisors – all part of the National Research School for Architecture and Planning in the Urban Landscape, APULA – set out to explore what may be considered the outback of Western Europe’s conurbations, the transnational region of Kiruna -Narvik.Both “remote” and “resourceful”, “threatened” and “thriving” (equally relative notions), this region seemed to offer possibilities to reflect upon many of the current tendencies influencing contemporary planning practice and research.